Enhancing Students' Mathematical Literacy through Ethnomathematics-Integrated Problem-Based Learning: A Study on Learning Independence - Amidi, Amidi; Kartono, Kartono; Mulyono, Mulyono; Pujiastuti, Emi (FKIP Universitas Lampung, 2025)
Enhancing Students' Mathematical Literacy through Ethnomathematics-Integrated Problem-Based Learning: A Study on Learning. This study addresses the issue of low mathematical literacy among junior high school students, particularly in relation to their learning independence. Objective: This study aims to (1) examine the effectiveness of the Problem-Based Learning (PBL) model integrated with an ethnomathematics approach in improving students’ mathematical literacy, (2) analyze the relationship between mathematical literacy and learning independence, and (3) analyze their literacy levels based on the degree of learning independence. This combination is important to investigate because it not only contextualizes mathematics within students’ cultural practices but also strengthens their learning independence, both of which are essential for the sustainable improvement of mathematical literacy. Method: A mixed-methods approach was employed using a sequential explanatory design. Quantitative analysis was conducted through a true experimental design with a posttest-only control group, while qualitative analysis was based on test results and interviews with students. Findings: The findings indicate that students in the experimental class using the ethnomathematics-based PBL model achieved higher mathematical literacy compared to those in the control class, which only used a Discovery Learning (DL) model. Additionally, learning independence has a positive effect on mathematical literacy. Students with high learning independence showed better fulfillment of literacy indicators, while those with medium and low learning independence showed varied levels of achievement in mathematical literacy. Conclusion: This study concludes that (1) the ethnomathematics-based PBL model is effective in improving mathematical literacy, (2) there is a relationship between mathematical literacy and learning independence, and (3) students with high, medium, and low learning independence have varying mathematical literacy. These findings highlight the importance of implementing a culturally integrated PBL model to enhance both cognitive and affective learning outcomes, while also emphasizing learning independence as an internal factor in supporting mathematical literacy development. Keywords: mathematical literacy, learning independence, PBL, ethnomathematics.